A case of retropharyngeal emphysema as a complication of pneumothorax. Issue 1 (20th November 2020) - Suda, Tsuyoshi; Yoneda, Tomoaki; Ichikawa, Yukari
Abstract: Retropharyngeal emphysema is a rare condition, and it is important to determine whether the patient presents with complications including pneumomediastinum or other severe clinical presentations such as an upper airway obstruction. In such cases, patients should undergo urgent tracheostomy and surgical neck drainage with concurrent administration of broad‐spectrum antibiotics. Abstract : Retropharyngeal emphysema is a rare condition, and it is important to determine whether the patient presents with complications including pneumomediastinum or other severe clinical presentations such as an upper airway obstruction. In such cases, patients should undergo urgent tracheostomy and surgical neck drainage with concurrent administration of broad‐spectrum antibiotics.